PENGARUH KUALITAS PELAYANAN JASA TRANSPORTASI TERHADAP KEPUASAN KONSUMEN (STUDI KASUS ARMADA BUS NPM BUKITTINGGI-JAKARTA) - Salsabila Rahmadani; Khadijah Nurani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2023)
The background of this research is related to the influence of the quality of transportation services on customer satisfaction of the Bukittinggi-Jakarta NPM bus. This study aims to determine the effect of service quality on customer satisfaction in the Bukittinggi-Jakarta NPM bus fleet. The method used in this study is to use quantitative methods. The sample used was 100 consumers of NPM Bukittinggi-Jakarta bus transportation services who made repeated purchases. The data used is the rimer obtained from the results of the questionnaire questionnaire. The sampling technique in this study used a simple random sampling method. Data collection was carried out using a questionnaire with a Likert scale with the SPSS 16 application. The data analysis technique used was Simple Linear Regression Analysis, Determination Coefficient Test, and T-test. significance of 0.000 ≤0.05. The test results for the coefficient of determination obtained R Square of 0.602. This shows that the dependent variable of customer satisfaction is 60.2% influenced by the independent variable service quality, while 39.8% is influenced by other variables that have not been studied in this study